2018
DOI: 10.4054/demres.2018.39.12
|View full text |Cite
|
Sign up to set email alerts
|

When working isn’t enough: Family demographic processes and in-work poverty across the life course in the United States

Abstract: BACKGROUND In-work poverty, a phenomenon that engenders social exclusion, is exceptionally high in the United States. The literature on in-work poverty focuses on occupational polarization, human capital, demographic characteristics, and welfare generosity. However, we have no knowledge on the effects of family demographic processes on inwork poverty across individuals' life courses. OBJECTIVE We estimate the risk of in-work poverty in the United States over the life course as a function of family demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…Similarly, substantial fatherhood premiums are evident longer in the early life courses of White and Hispanic men than in the lives of Black men. This highlights the potential caveats of estimating the effects of parenthood on wages averaged across age groups (see Van Winkle & Struffolino, 2018 for a similar argument related to in‐work poverty). Both our motherhood penalties and fatherhood premiums would be considerably underestimated had we not focused on age heterogeneity.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, substantial fatherhood premiums are evident longer in the early life courses of White and Hispanic men than in the lives of Black men. This highlights the potential caveats of estimating the effects of parenthood on wages averaged across age groups (see Van Winkle & Struffolino, 2018 for a similar argument related to in‐work poverty). Both our motherhood penalties and fatherhood premiums would be considerably underestimated had we not focused on age heterogeneity.…”
Section: Resultsmentioning
confidence: 88%
“…However, German labor market and family policy also actively incentivizes a male-breadwinner female-homemaker division of labor with low coverage of all-day childcare and schooling. Differences in the realization of children's genetic potential by household composition may be larger in liberal societies, such as the United States, where women are at a considerably higher risk of poverty following divorce (Van Winkle & Struffolino, 2018). Compared to social democratic states where social systems secure divorced women's socioeconomic well-being and facilitate labor market participation, such as Sweden, differences in the heritability may be lower.…”
Section: Discussionmentioning
confidence: 99%
“…This shift towards a life course approach to poverty is also evident in a few recent scholarly research focusing on in-work poverty. Van Winkle and Struffolino (2018) showed that the association between family demographic transitions in the US (e.g. marriage and divorce) and the probability of in-work poverty vary across the life course.…”
Section: A Life Course Approach To In-work Povertymentioning
confidence: 99%
“…Despite the necessity to account for the temporal dynamics of in-work poverty, most research is cross-sectional and either studied the association between in-work poverty and individual characteristics, such as education, gender and race, or macro-level factors, such as union density or welfare state generosity (see Kenworthy and Marx [2018] for a review). The few longitudinal accounts of in-work poverty studied the probability of entering and exiting the working poor as a function of changes in employment status and family structure across the life course (Hick and Lanau 2018;Barbieri, Cutuli, and Scherer 2018;Gutiérrez, Ibáñez, and Tejero 2011;Tejero 2017;Van Winkle and Struffolino 2018). Yet no research to date has analyzed individuals' pathways after exiting in-work poverty.…”
Section: Introductionmentioning
confidence: 99%